Awareness and use of electronic resources by faculty members of the Ghana Communication Technology University: a case study of the Accra campus - Anguah, Philip Larry (Department of Knowledge and Information Stewardship, 2025)
In view of the application of information communication technologies in academic libraries as well as the importance of electronic resources to academic work, the objective of this study was to examine the level of awareness and the extent of use of library electronic resources by faculty members at the Ghana Communication Technology University (GCTU), Accra campus. In addressing this objective, the following critical questions were generated: What is the level of awareness of Accra campus faculty members of the GCTU Library's electronic resources? What is the extent of use by Accra campus faculty members of the GCTU Library's electronic resources? For what possible purposes would faculty members use the GCTU Library's electronic resources? What is the level of satisfaction by Accra campus faculty members in using the GCTU Library electronic resources? What are possible constraints faced by Accra campus faculty members in using the GCTU Library's electronic resources? The Technology Acceptance Model (TAM) was used to provide theoretical support for the study. Motivated by the pragmatic paradigm, the study used a convergent parallel mixed methods strategy to collect data, employing both quantitative and qualitative approaches. Adopting a single case study design, this study used GCTU, Accra campus as its case to respond to the critical questions. In addressing the study's objective, a descriptive survey and an interview research method were used to collect data from a census of 122 faculty members at the Accra campus and purposively selected library staff members, respectively. Data was collected by a face-to-face interaction through structured questionnaire delivery and collection and the conducting of semi-structured interviews. Data collected from the questionnaire and interviews was analyzed using SPSS and NVivo, respectively. The study found that most faculty members at GCTU Library are aware of e-resources such as Emerald, IEEE Xplore, JSTOR, and EBSCOhost, primarily used for research and publication. They prefer e-resources over printed equivalents due to their ease of use. However, constraints such as slow internet, information overload, and power outages hinder their use. The study recommends increased awareness, faculty training, and strengthening internet connectivity for optimal use of GCTU Library e-resources. This study has relevance and significance for LIS professional practice, disciplinary theory/knowledge growth, research methodology, and university policy development.